The Enhanced Human: Exploring what it means to be enhanced and the ethical issues around human enhancement technology use within the military and sports - Cho, Seoyeon Andrea (Wake Forest University, 2023)
With technology continuing to evolve every day, advanced human enhancement technologies become closer to being a common aspect of our daily reality. The main purpose of this thesis is to discuss the many complexities of human enhancement and delve further into the ethical issues related to human enhancement technology use specifically in the military and sports. I begin with a broad discussion of human enhancement and then narrow the scope to how human enhancement technologies have been used in the military and sports. I follow with a focus on the ethical issues raised by human enhancement technology use in these two areas, respectively. I conclude with a summary of the main takeaways and pose questions for further consideration regarding the future trajectory of human enhancement. The goal of this thesis is not to provide a clear answer on what is human enhancement and how should it be considered within the military and sports. Rather, it is to establish a foundational discussion of human enhancement as well as the context-specific ethical issues in the hopes that it will lay the groundwork for subsequent research in these areas.